Soil testing for plant nutrient management - International Water Management Institute (International Water Management Institute, 2025)
This video shows farmers how to take soil samples for testing and is produced by the International Water Management Institute in partnership with Sri Lanka’s Department of Agriculture and the World Vegetable Center under the CGIAR Better Diets and Nutrition Program.